2009
DOI: 10.1289/ehp.11681
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Prenatal Exposure to Perfluorinated Chemicals and Reduced Fetal Growth

Abstract: BackgroundPerfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) are man-made, ubiquitous, and persistent contaminants in the environment, wildlife, and humans. Although recent studies have shown that these chemicals interfere with fetal growth in humans, the results are inconsistent.ObjectivesOur goal was to investigate the correlation between relatively low levels of PFOS and PFOA in maternal serum and birth weight and birth size.MethodsWe conducted a hospital-based prospective cohort study between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
168
5
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 262 publications
(192 citation statements)
references
References 46 publications
16
168
5
2
Order By: Relevance
“…In 2002, the Hokkaido University Graduate School of Medicine established a hospital-based prospective cohort study entitled the "Hokkaido Study on Environment and Children's Health" to investigate the possible adverse effects of PCBs, PCDDs/PCDFs, perfluorinated chemicals, and many other environmental contaminants on fetal growth and neurodevelopment Sasaki et al, 2008;Nakajima et al, 2006;Washino et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…In 2002, the Hokkaido University Graduate School of Medicine established a hospital-based prospective cohort study entitled the "Hokkaido Study on Environment and Children's Health" to investigate the possible adverse effects of PCBs, PCDDs/PCDFs, perfluorinated chemicals, and many other environmental contaminants on fetal growth and neurodevelopment Sasaki et al, 2008;Nakajima et al, 2006;Washino et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…8 Inoue et al 18 were the first to report the presence of PFCs in human maternal and cord blood samples, and several other studies followed. [19][20][21] Furthermore, recent epidemiological studies in Denmark, USA and Japan [21][22][23] have investigated possible adverse effects of PFCs on the foetus. In the Danish cohort they found an inverse association between maternal PFOA concentration and birth weight.…”
mentioning
confidence: 99%
“…Scholars have previously shown that environmental chemicals have been detected in virtually all pregnant women in the USA (e.g., Woodruff et al 2011b) with animal and human evidence suggesting links between chemical exposures and reductions in fetal growth (Fei et al 2008;Washino et al 2009;Kodavanti et al 2010;Harley et al 2011). In vivo and in vitro animal studies, for example, show adverse developmental and reproductive effects from chemicals such as brominated flame retardants found in consumer products (Schecter et al 2005).…”
Section: Chemical Presence In Bodiesmentioning
confidence: 99%